APPEAL OBJECTS IN UZBEK WOMEN'S POETRY (BELOVED, GOD, NATURE...) - Nabiyeva Nodira Saidovna (Western European Studies, 2025)
This article explores the objects of appeal in the poetry of Uzbek female poets, focusing on the themes of beloved, God, and nature. Through the works of renowned poets such as Zulfiya Isroilova, Saida Zununova, Xalima Xudoyberdiyeva, and Halima Ahmedova, we analyze the emotional depth, delicate feelings, and unique expressions of women's poetic creativity. The selection of female poets in this study is not incidental, as the concept of appeal is often associated with vulnerability and delicacy—traits traditionally linked to women's nature. Therefore, women's poetry plays a leading role in expressing these appeal objects. As you read this article, you will further realize this perspective
Keywords: Appeal; beloved; God; nature